2020
DOI: 10.3389/fgene.2019.01307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SNPs in HSP Family Genes, Variation in the mRNA and Intracellular Hsp Levels in COPD Secondary to Tobacco Smoking and Biomass-Burning Smoke

Abstract: Heat shock proteins (HSP) genes are a superfamily responsible for encoding highly conserved proteins that are important for antigen presentation, immune response regulation, and cellular housekeeping processes. These proteins can be increased by cellular stress related to pollution, for example, smoke from biomass burning and/or tobacco smoking. Single nucleotide polymorphisms (SNPs) in these genes could affect the levels of their proteins, as well as the susceptibility to developing lung diseases, such as chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
(49 reference statements)
0
18
0
Order By: Relevance
“…Unfortunately, in the southern region even though Amerindian contribution predominates, this exposed group was women in charge of household chores, among which is cooking, an activity in which they use wood (primarily) to start and maintain the combustion of biomass to heat food, as we have previously reported. 39 For that reason, the biomass burning-smoke group had a predominance of females.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in the southern region even though Amerindian contribution predominates, this exposed group was women in charge of household chores, among which is cooking, an activity in which they use wood (primarily) to start and maintain the combustion of biomass to heat food, as we have previously reported. 39 For that reason, the biomass burning-smoke group had a predominance of females.…”
Section: Discussionmentioning
confidence: 99%
“…Based on genotype analysis, we selected a subsample of participants for more in-depth characterization. To obtain sputum, we followed a previously published protocol [ 15 ]; briefly, participants were treated with a nebulizer with a sterile 7% saline solution. Treatment lasted for 5 min followed by a rest period of 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Although it has been reported that some genes involved in inflammation are associated with respiratory diseases [ 87 , 88 , 89 , 90 , 91 , 92 ], investigations regarding genetic factors involved in the susceptibility and severity are scanty. Two primary examples in inflammatory response genes, where genetic variability is associated with an altered phenotype, are TNF-α and IL-1β; both are pleiotropic modulators critical in regulating inflammation.…”
Section: Genetic Variants and Influenza A H1n1 Virus Infectionmentioning
confidence: 99%